Effects of Different Tillage, Rotation Systems and Nitrogen Levels on Wheat Yield and Nitrogen Use Efficiency - Nihal Kayan; Nazife Gözde Ayter Arpacıoglu; Imren Kutlu; Mehmet Sait Adak (Turkish Journal of Agriculture: Food Science and Technology)
This research was conducted between 2011 and 2015 at research field of Faculty of Agriculture, Eskişehir Osmangazi University for evaluating two tillage methods (conventional and reduced), three crop rotations (wheat-wheat; wheat-fallow; wheat-chickpea) and four N levels (0, 50, 100, 150 kg ha-1). The experimental design was split-split plot with three replicates. Tillage methods were in main plots, crop rotations in subplots and N levels in sub-sub plots. The N concentration of grain and straw harvested from aboveground plant organs was separately determined using by the Kjeldahl digestion method after the plant samples were ground. Then, grain protein content, nitrogen use efficiency (NUE), nitrogen uptake efficiency (NUPE), nitrogen utilization efficiency (NUTE) were calculated. According to results, effects of tillage methods on NUE were unclear. Conventional tillage methods resulted in higher NUPE than reduced tillage in the last three years of the experiment. The NUTE was higher in reduced tillage than conventional in 2011-2012 and 2014-2015. The effects of tillage methods on grain yield were different due to the climatic conditions. Wheat-chickpea rotation had the better results for examined traits in this research. Increasing nitrogen doses increased grain and plant protein rate, however it decreased NUE and NUPE. The effects of nitrogen doses on NUTE were ambiguous. Nitrogen use efficiency and NUPE is traits that can be differed according to changeable grain yield depend on environmental conditions. Therefore, the experiments should be conducted for more than four years for revealed absolute effects both soil tillage method and nitrogen fertilization.